USE OF FUZZY LOGIC IN WIRELESS COMMUNICATION: SURVEY - Mohsin N. AL-Maliki; Hasanain A. H. Al-Behadili; Reihaneh Tati (Journal Park Publishing, 2023)
Fuzzy logic has played a significant role in various sectors of science. It can be seen its application in most of modern sciences. One updating field is the wireless communications. The application of Fuzzy logic in wireless communications has a particular relevance with the improvement of prediction and estimation. There are different applications of such topic such as: channel estimation, decoding and equalization. This paper presents many usages of Fuzzy logic in the field of wireless communications. In fact, it has taken recent studies which have discussed such application.